Almost there and almost not - Urban, Linda (Atheneum Books for Young Readers, 2021)
When her father goes away, eleven-year-old California "Callie" Poppy winds up with her eccentric Great-Aunt Monica and their ancestor, the once-famous etiquette expert Eleanor Fontaine, now a hypersensitive ghost.